2018
DOI: 10.1016/j.carbpol.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the antifungal activity of amphiphilic derivatives of diethylaminoethyl chitosan against Aspergillus flavus

Abstract: In this study, the antifungal activity of chitosan derivatives against A. flavus was studied to understand the contribution of the molecular mass (Mw) and of the hydrophobic and electrostatic forces to the inhibition of fungal growth. The interaction of amphiphilics ranging from 8 to 130 kDa with model membranes of zwitterionic L-α-phosphatidylcholine (PC) and anionic L-α-phosphatidylcholine/L-α-phosphatidyl-DL-glycerol (PC:PG, 80:20 mol%) were exploited to obtain information on the inhibition mechanism. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Both spore germination and mycelial growth were inhibited by chitosan clearly demonstrating its effects on various growth and development stages of P. expansum. Similar antifungal activities of chitosan against other plant pathogenic fungi have been observed, such as F. oxysporum (Palma-Guerrero et al, 2008), A. parasiticus (Cota-Arriola et al, 2011) and A. flavus (Dias et al, 2018). Moreover, about 60% spore germination and mycelium growth of P. expansumin in liquid medium were inhibited by chitosan at concentration of 0.05%, which is very close to the observed 50% inhibition concentrations of chitosan for Alternaria alternate, F. oxysporum and Pythium debaryanum (Rabea & Steurbaut, 2010).…”
Section: Effect Of Chitosan On Spore Germination and Fungal Growthsupporting
confidence: 66%
See 1 more Smart Citation
“…Both spore germination and mycelial growth were inhibited by chitosan clearly demonstrating its effects on various growth and development stages of P. expansum. Similar antifungal activities of chitosan against other plant pathogenic fungi have been observed, such as F. oxysporum (Palma-Guerrero et al, 2008), A. parasiticus (Cota-Arriola et al, 2011) and A. flavus (Dias et al, 2018). Moreover, about 60% spore germination and mycelium growth of P. expansumin in liquid medium were inhibited by chitosan at concentration of 0.05%, which is very close to the observed 50% inhibition concentrations of chitosan for Alternaria alternate, F. oxysporum and Pythium debaryanum (Rabea & Steurbaut, 2010).…”
Section: Effect Of Chitosan On Spore Germination and Fungal Growthsupporting
confidence: 66%
“…Chitosan, the deacetylation product of chitin, has been recently used as a promising alternative postharvest diseases management. Diverse studies have shown the efficiency of chitosan in controlling postharvest rot of horticultural commodities caused by plant pathogenic fungi, such as Aspergillus flavus (Dias et al, 2018), Botrytis cinerea (Lopes et al, 2014), Ceratocystis fimbriata (Xing et al, 2018), Pilidiella granati (Munhuweyi et al, 2017) and P. expansum (Wang et al, 2014). On addition to its potential to elicit plant defense by increasing the production of defense-related secondary metabolites and promoting the expression of defense-related enzymes (Hadwiger, 2013), chitosan also exhibits direct antimicrobial activities against plant pathogens (Xing et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…S5 in Supplementary data) (Gabriel, Tiera, & Tiera, 2015). More recently, a series of chitosan derivatives of various Mw and fixed contents of DEAE and hydrophobic groups were reported by the same lab to study the mechanism of the antifungal properties against A. flavus (Dias et al, 2018). Similarly, the introduction of DEAE groups alone did not significantly improve the antifungal activity of chitosan, but the subsequent hydrophobic modification of chitosan with dodecyl groups improved the antimicrobial activity accordingly.…”
Section: Introducing Polyamino Groupsmentioning
confidence: 96%
“…The film for the amphiphilic derivative DEAE-CH-Dod displayed a similar coloration to that of CH C , while the former still exhibited a higher b* value (Table 5 and Table S2). This improvement resulted from the reductive environment provided by NaBH 4 used in the reductive amination step with dodecyl groups [23].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, it was hypothesized that low molecular weight amphiphilic derivatives of chitosan could be used to form films with improved antimicrobial activity against some common fungi. A derivative with low molecular weight (Mw), and containing diethylaminoethyl (DEAE) groups was selected because of its high activity against the fungi of the genus Aspergillus [22,23]. A comparative study was performed using chitosan of varied Mw for the preparation of films with the aims of investigating the film properties and their antifungal action against the fungi Aspergillus flavus , Alternaria solani , Alternaria alternate , and Penicillium expansum .…”
Section: Introductionmentioning
confidence: 99%